MODEL PENDIDIKAN KARAKTER DI PESANTREN - Toto Rahardjo (Akademika, 2017)
The goal of this research is to get description (qualitative description) ofCharacter education in a Peranstren; which is Modern Pesantren (dormitory) Al-Hassan,PondokGede, Bekasi. The focus of this research is Character Education Design atPesantren Al-Hassan, Pondok Gede, with the target of the 1st grade students of Junior HighSchool. The Methods of research conducted were qualitative, where all the data was takenby observation, interview, and documentation study.From the result , we can see thatcharacter education design at Pesantren Al-Hassan is carry out by making variousprograms and activities related to the students , for example: boy scout, sport, etc. Thanthey report routinely to their ustadz (teacher), who nurtures them generally or on a certainextent.This Research gives recommendation, in a form of conclusions and suggestions to thePesantren‘ssupervisorandstakeholderstomakethiseducationcharacterdesignthathasbeen running well, be balanced by good administration and management concept as well asa better management strategy, as an effort to maximize the process of reaching the goal andperspectives of the Pesantren toward the sudents